ANALISIS LAPORAN HARGA POKOK PRODUKSI (STUDI KASUS PADA USAHA PENGOLAHAN MINYAK KELAPA MANDAR DIKABUPATEN MAJENE) - Dahlia Dahlia; Nuraeni M (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
Coconut oil Mandar processing business is one of the typical products of Majene Regency which has a special flavor and it is generally produced traditionally with one of the main superiority that is free from preservatives. In general, coconut oil processing center produces the main products in the form of coconut oil and by products are quite varied. This research aim to find the application of the cost of production of Mandar Coconut Oil Processing Business In Majene Regency). The data used are primary data and secondary data. The data collection technique is interviews, observation and documentation. The analytical method used are qualitative descriptive analysis. The results showed that the cost of production of Mandar Coconut Oil for each production (assuming 150 coconuts) which is Rp. 370,000 / day / every time production in 2018.